2005
DOI: 10.1002/pmic.200401005
|View full text |Cite
|
Sign up to set email alerts
|

Pressure overload and neurohumoral activation differentially affect the myocardial proteome

Abstract: Treatment with monocrotaline causes pulmonary hypertension in rats. This results in severe pressure overload-induced hypertrophy of the right ventricles, whilst the normally loaded left ventricles do not hypertrophy. Both ventricles are affected by enhanced neuroendocrine stimulation in this model. We analyzed in this model load-induced and catecholamine-induced changes of right and left ventricular proteome by two-dimensional gel electrophoresis, tryptic in-gel digest, and matrix-assisted laser desorption/ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…The slower b-isoform was increased in the LV of both MCT-4 and MCT-6, as previously reported in different models of RV hypertrophy [17,43,46,47]. Changes in the expression of enzymes involved in bioenergetics and cell metabolism such as pyruvate dehydrogenase kinase-4, acetyl-CoA dehydrogenase and mitochondrial ATP synthase [42,43] as well as a reduced capillary proliferation [21] have also been described in the LV of PH rats. Contrastingly, calcium kinetics side, diastolic pressures are nicely matched at all afterload levels in the control animal, but become progressively higher as afterload increases, both in MCT-4 and MCT-6 animals.…”
Section: Edlvp) B End Diastolic LV Dimensions (Edlvd)supporting
confidence: 60%
See 2 more Smart Citations
“…The slower b-isoform was increased in the LV of both MCT-4 and MCT-6, as previously reported in different models of RV hypertrophy [17,43,46,47]. Changes in the expression of enzymes involved in bioenergetics and cell metabolism such as pyruvate dehydrogenase kinase-4, acetyl-CoA dehydrogenase and mitochondrial ATP synthase [42,43] as well as a reduced capillary proliferation [21] have also been described in the LV of PH rats. Contrastingly, calcium kinetics side, diastolic pressures are nicely matched at all afterload levels in the control animal, but become progressively higher as afterload increases, both in MCT-4 and MCT-6 animals.…”
Section: Edlvp) B End Diastolic LV Dimensions (Edlvd)supporting
confidence: 60%
“…ACE mRNA levels progressively increased in MCT-4 and MCT-6, whereas ET-1 mRNA levels were only increased 6 weeks after MCT injection P \ 0.05: * vs. Ctrl-4; vs. Ctrl-6; à vs. regulator proteins such as the Ca 2? -ATPase of the sarcoendoplasmic reticulum and phospholamban were consistently reported to be unaltered in the non-overloaded LV [21,42,43]. To further explore the underlying mechanisms of LV myocardial dysfunction, we investigated neurohumoral activation, extracellular matrix composition and apoptosis.…”
Section: Edlvp) B End Diastolic LV Dimensions (Edlvd)mentioning
confidence: 99%
See 1 more Smart Citation
“…20 Seyfarth et al have reported downregulation of the 1,2 receptor-Gs protein-adenylyl cyclase system in both ventricles, although the change in the RV was more prominent than in the LV. 19 As shown in Fig 2, and by Kögler et al, 21 the plasma NA level was significantly increased in MCT-treated rats, suggesting that the downregulation of the adrenergic -receptor may be in part due to catecholamine overload.…”
Section: Role Of Upregulated Neurohumoral Factors In Ventricular Hypementioning
confidence: 99%
“…However, the role of BRCA1 in protecting cardiac tissue from DNA damage has not been fully explored to date. In a recent study, Gerd Hasenfuss et al 11. described, for the first time, a potentially novel signaling pathway (BRAP2/BRCA1) that was involved in the process of myocardial hypertrophy.…”
mentioning
confidence: 99%